Pengenalan Perbanyakan Bibit Tanaman Buah Secara Vegetatif Kepada Masyarakat Desa Tabalagan - Edi, Syahrial; Fariadi, Herri (Universitas Dehasen Bengkulu, 2024)
This Thematic Real Work Lecture (KKN) Work Program in Universitas Dehasen Bengkulu 2023 was held at the Department of Food Crops Horticulture and Plantations UPTD BITPHPP in Tabalagan Village, Semidang Lagan District, Central Bengkulu Regency, Bengkulu Province. The work program carried out during this KKN period is